Influence of mix design on the carbonation, mechanical properties and microstructure of reactive MgO cement-based concrete - Ruan, Shaoqin (2017)
This study assesses the influence of mix design on the hydration and carbonation of reactive MgO cement (RMC)-based concrete formulations by varying the water and cement contents. Samples were subjected to accelerated carbonation under 10% CO2 for up to 28 days and compared with corresponding PC-based samples. Their performance was analyzed by compressive strength, porosity, density, water sorptivity and thermal conductivity measurements. XRD, TGA/DSC and FESEM/SEM analyses were employed to investigate the formation of hydration and carbonation products and microstructural development. RMC samples achieved 28-day strengths of 62 MPa, which was comparable with PC samples. Strength gain of RMC samples was accompanied with a substantial decrease in porosity, determined by the amount and morphology of carbonates. The initial water content was more influential on final performance and thermal conductivity than cement content. Lower water contents led to higher strengths due to lower porosities and faster CO2 diffusion within dry mediums.